ACCUMULATION OF CHLOROFORM USING HYDROBIONTS FOR THE PURIFICATION OF NATURAL WATER WHEN PREPARING DRINKING WATER - Kuvatovich, Aliev Malhmud; Ernazarovna, Maxmudova Dildora; Abduvalievna, Najmiddinova Nigora (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the analysis of a series of experiments to study the accumulation of chloroform using algae. The accumulating ability of the natural biocenosis for the retention of mineral, organic and biological pollution was studied.